Perceived Effect of Fuelwood Utilization on Climate Change by Rural Dwellers in Northwestern Nigeria - Adamu, Comfort Oyekale; Alarima, Cornelius Idowu (American Journal of Human Ecology, 2013)
<!–[if gte mso 9]> <![endif]–> Creating awareness among people especially rural dwellers in Nigeria about appropriate activities required in terms of mitigating climate change is imperative. This paper discusses climate change in relation to its causes and the perceived effect of fuelwood utilization by rural dwellers in Kebbi, Sokoto and Zamfara states. The study used data from 360 rural people proportionately selected according to the number of agricultural cells of each of the states by simple random sampling. Regression analysis was used to determine the relationship between study variables. Results show respondents age ranged between 20 and 80 years, with a mean of 36.73. They had Quranic education, seasonal contact with extension agents and low awareness of perceived environmental effect of fuelwood utilization. In addition, the study revealed that there is significant relationship between the perceived environmental effect of fuelwood acquisition and age (β= -0.159; p<0.01), educational level (β= 0.461; p<0.01), contact with extension (β= 0.249; p<0.01) and awareness (β= 0.481; p<0.01). These findings suggest the need for environmental education and consciousness. The study then concludes that agricultural extension programmes in rural communities must be made effective in enlightening the people about environmental consequences of fuelwood utilization and its implication on climate change. The implication of the study is that the higher the level of contact of rural dwellers with extension agents, the higher their awareness of the effect of fuelwood utilization. It also implied that the higher the level of awareness of the rural dwellers the higher their perception of the effect of fuelwood utilization on the environment. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>